2019
DOI: 10.1007/jhep10(2019)286
|View full text |Cite
|
Sign up to set email alerts
|

Topological recursion in the Ramond sector

Abstract: We investigate supereigenvalue models in the Ramond sector and their recursive structure. We prove that the free energy truncates at quadratic order in Grassmann coupling constants, and consider super loop equations of the models with the assumption that the 1/N expansion makes sense. Subject to this assumption, we obtain the associated genus-zero algebraic curve with two ramification points (one regular and the other irregular) and also the supersymmetric partner polynomial equation. Starting with these polyn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(48 citation statements)
references
References 34 publications
0
48
0
Order By: Relevance
“…Let us collect the coefficients of t l 1 and t l 2 in (2.12) and set to zero, respectively, we obtainC 17) and the recursive relations…”
Section: Jhep11(2020)119mentioning
confidence: 99%
See 1 more Smart Citation
“…Let us collect the coefficients of t l 1 and t l 2 in (2.12) and set to zero, respectively, we obtainC 17) and the recursive relations…”
Section: Jhep11(2020)119mentioning
confidence: 99%
“…The supereigenvalue models have attracted considerable attention. They can be regarded as supersymmetric generalizations of matrix models [1]- [17]. Many of the important features of matrix models, such as the Virasoro constraints, the loop equations, the genus expansions and the moment descriptions have their supersymmetric counterparts in the supereigenvalue models.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus conceivable that results concerning Airy structures (and their supersymmetric generalizations [19], related to supereigenvalue models and the corresponding topological recursion [20][21][22][23][24]) may find applications in some of the subjects listed above.…”
Section: Introductionmentioning
confidence: 99%
“…However, such relations are obscure, even though corresponding supersymmetric structures in matrix models are known. Indeed, supersymmetric generalizations of matrix models, referred to supereigenvalue models, have been introduced and discussed some time ago [3,8], and also more recently [20,[26][27][28]61]. By construction, loop equations for such supereigenvalue models can be rewritten in the form of super-Virasoro constraints.…”
Section: Introductionmentioning
confidence: 99%
“…This generalizes the reformulation of loop equations in terms of Virasoro constraints in the non-supersymmetric case, and thus one might hope that super-Virasoro constraints for supereigenvalue models lead immediately to supersymmetric topological recursion. However, in [ 20 , 61 ] it was shown that such a generalization is not automatic: one can indeed write down a recursive system that determines the partition function of a supereigenvalue model, but it is augmented by an auxiliary equation, which does not have a simple interpretation. In a sense, this makes the super quantum Airy structures that we introduce here even more interesting, and revealing their meaning in the context of supereigenvalue models is an important task.…”
Section: Introductionmentioning
confidence: 99%